Entropy generation in water conveying nanoparticles flow over a vertically moving rotating surface: Keller box analysis - Kumar, Sanjay; Sharma, Kushal; Makinde, Oluwole Daniel; Joshi, Vimal Kumar; Saleem, Salman (International journal of numerical methods for heat & fluid flow, 2024)
Purpose The purpose of this study is to investigate the entropy generation in different nanofluids flow over a vertically moving rotating disk. Unlike the classical Karman flow, water-based nanofluids have various suspended nanoparticles, namely, Cu, Ag, Al2O3 and TiO2, and the disk is also moving vertically with time-dependent velocity. Design/methodology/approach The Keller box technique numerically solves the governing equations after reduction by suitable similarity transformations. The shear stress and heat transport features, along with flow and temperature fields, are numerically computed for different concentrations of the nanoparticles. Findings This study is done comparatively in between different nanofluids and for the cases of vertical movement of the disk. It is found that heat transfer characteristics rely not only on considered nanofluid but also on disk movement. Moreover, the upward movement of the disk diminishes the heat-transfer characteristics of the fluid for considered nanoparticles. In addition, for the same group of nanoparticles, an entropy generation study is also performed, and an increasing trend is found for all nanoparticles, with alumina nanoparticles dominating the others. Originality/value This research is a novel work on a vertically moving rotating surface for the water-conveying nanoparticle fluid flow with entropy generation analysis. The results were found to be in good agreement in the case of pure fluid.